2022
DOI: 10.3390/cells11071150
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Remodeling of the Neuromuscular Junction with Aging

Abstract: Aging is associated with gradual degeneration, in mass and function, of the neuromuscular system. This process, referred to as “sarcopenia”, is considered a disease by itself, and it has been linked to a number of other serious maladies such as type II diabetes, osteoporosis, arthritis, cardiovascular disease, and even dementia. While the molecular causes of sarcopenia remain to be fully elucidated, recent findings have implicated the neuromuscular junction (NMJ) as being an important locus in the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 132 publications
(183 reference statements)
1
14
0
Order By: Relevance
“…70,71 Recent findings have implicated the neuromuscular junction to be an important locus in the development and progression of sarcopenia, while it is still unclear whether glutamate is involved in the adaptive remodeling of the neuromuscular junction in patients with sarcopenia. 72 Altogether, the current evidence supports that the change in glutamate metabolism level is one of the reasons for the decrease in muscle energy metabolism. However, whether glutamate can become a potential therapeutic product to improve the symptoms of sarcopenia remains a question for further research.…”
Section: Glutamatesupporting
confidence: 59%
“…70,71 Recent findings have implicated the neuromuscular junction to be an important locus in the development and progression of sarcopenia, while it is still unclear whether glutamate is involved in the adaptive remodeling of the neuromuscular junction in patients with sarcopenia. 72 Altogether, the current evidence supports that the change in glutamate metabolism level is one of the reasons for the decrease in muscle energy metabolism. However, whether glutamate can become a potential therapeutic product to improve the symptoms of sarcopenia remains a question for further research.…”
Section: Glutamatesupporting
confidence: 59%
“…268,269 Ageing has many adverse effects on NMJs, with consequences for sarcopenia and neurodegenerative diseases like ALS. 270 The changes during normal human age-related loss of muscle mass and function (i.e., sarcopenia) 7,271 correspond with changes during normal ageing of rodents. Transcriptome analyses identified early denervation of muscles associated with the onset and progression of sarcopenia in mice and rats from about 15 months of age, as well as changes in metabolism and ECM composition.…”
Section: Nerves (And Vulnerability Of Fast Motoneurons)mentioning
confidence: 99%
“…During normal ageing of the peripheral nervous system, there is increasing loss of motor units, axonal atrophy, demyelination caused by oxidative damage to proteins and lipids, and modified transmission of the electrical signal through the NMJ. 270,278 However, it remains unclear whether sarcopenia is initiated and driven primarily by changes in nerves or muscles. Though, neuronal differences contribute to manifestation of many specific neuromuscular disorders.…”
Section: Nerves (And Vulnerability Of Fast Motoneurons)mentioning
confidence: 99%
See 1 more Smart Citation
“…Deschenes et al ( 24 ) proposed that acetylcholine release increased in aged muscles leading to a faster rate of neuromuscular fatigue. It has been suggested that decreasing ACh may be an effective remedy to treat structural changes in NMJ that can lead to sarcopenia ( 25 ).…”
Section: Neuromuscular Junction Lesionmentioning
confidence: 99%